Australian Institute of Sport Chief Medical Officer Dr David Hughes answers your questions (News Corp Australia Network, 2020)
Australian Institute of Sport Chief Medical Officer Dr David Hughes answers questions concerning COVID-19, COVID-19 restrictions and return to sport: